THE IMPLEMENTATION OF SHOW AND TELL TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILL - Putri, Aprilia Riyana (Universitas Islam Nahdlatul Ulama Jepara, 2023)
In teaching and learning process, the suitable technique has a good impact for the students’ ability. Here, the researchers focus on how to implement show and tell technique in teaching speaking because the most appropriate one for describing things as the topic for better understanding and to foster effective communication in the classroom. This research employed a qualitative study by using a classroom action research which was done during for 2 cycles. Each of the cycle was done in two meetings. Data were collected through the observation sheet, field notes, interview and tests. The research findings showed that there were some improvement on students’ speaking skill. In cycle one, the process of teaching learning with Show and Tell technique suggested a potential improvement, the researchers found some minor technical problems and weaknesses. After that, many revision were done and later applied in cycle two. The result of the research showed that the students have some improvements during the process of teaching and learning when show and tell technique was implemented. The students’ participation, pronunciation, fluency and vocabulary mastery were increased; they were more active, enthusiastic, and more confident in practicing speaking in intensive speaking class